Analisis Studi Kelayakan Bisnis Dilihat Dari Aspek Finansial Pada PT. Belayan International Coal Di Muara Badak Pada Masa Pandemi Covid-19 - Lenny Nopianingsih; yonathan palinggi; Johansyah Johansyah (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract : The purpose of this study was to determine and examine the business prospects of PT. Belayan Internasional Coal in Muara Badak is seen from the aspect of financial analysis. The data used are financial statements for 2015 - 2019. The analytical tools used are Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (BCR) and Payback Period. Net Present Value (NPV) results from PT. International Coal Belayan in Muara Badak Rp. 5,513,858,194. So that each year a different cash value is obtained. In the fifth year, the final value of the Net Present Value (NPV) is positive > 0 and this value is still greater than the investment value that has been invested by PT. International Coal Belayan in Muara Badak Rp. 5,500,000,000. he resulting Internal Rate of Return (IRR) value is 21.48%. Because this value is greater than the bank interest rate of 5%. The IRR is greater than the applicable discount factor (rate), which is 5 percent. The value of Benefit-Cost Ratio (BCR) is 1.033. The BCR value means that the value of the benefits obtained in the business of PT. International Coal Belayan in Muara Badak is 1,033 times the value of the costs incurred at an interest rate of 5%. From the results of the analysis, the investment that has been invested in the business of PT. International Coal Belayan in Muara Badak Rp. 5,500,000,000 and it is estimated that the company can return in 5 years, in fact it can be returned in only 2 years 5 months. The payback period is only 50% of the 5 years estimated by PT. International Coal Belayan in Muara Badak.